Time is of the essence: Direct and indirect effects of plant ontogenetic trajectories on higher trophic levels - Quintero, Carolina (2014)
Physiological and morphological constraints during plant ontogeny affect the expression of numerous plant traits relevant to higher trophic levels, such as nutritional content and physical and chemical defenses. Yet we know little about how temporal variation in these traits can directly and/or indirectly mediate tri-trophic interactions, such as those between plants, their herbivores, and herbivore natural enemies. Using four distinct ontogenetic stages of Plantago lanceolata (Plantaginaceae) and the specialist herbivore Junonia coenia (Lepidoptera, Nymphalidae), we evaluated how ontogenetic changes in plant quality can: (1) directly alter plant-herbivore interactions through butterfly oviposition choice and caterpillar performance assays, and (2) indirectly alter herbivores susceptibility to higher trophic levels through caterpillars iridoid glycoside sequestration and immune defenses. Results showed that plant defensive traits increased over P. lanceolata development, with leaf tissues becoming tougher and plant allelochemicals (iridoid glycosides) occurring in higher amounts. Conversely, plant nutritional quality (water and nitrogen content) decreased as plants aged. These ontogenetic trajectories strongly altered both direct and indirect interactions between plants and higher trophic levels. Buckeye butterflies showed a stronger oviposition preference for younger developmental stages of P. lanceolata, laying on average 60% more eggs on juvenile than on reproductive plants. Feeding experiments with caterpillars showed that larvae feeding on juvenile plants showed faster relative growth rate and increased digestive efficiency compared with those feeding on plants in the reproductive stage. These individuals, however, acquired lower levels of sequestered chemical defenses than did those feeding on older P. lanceolata plants, potentially rendering them more susceptible to predation. Finally, host plant age altered the ability of a caterpillar to mount an immune response against simulated parasitoid eggs. Specifically, caterpillars reared on older plant life stages, and thus with higher levels of sequestered iridoid glycosides, showed a compromised immune response compared to those feeding on younger plant age classes. This study exemplifies how ontogenetic trajectories in plant traits can scale up to directly or indirectly alter tri-trophic interactions, which may have key implications for understanding temporal shifts in herbivore population and community structure.